Organizational factors and process capabilities in a KM strategy: toward a unified theory - Valaei, Naser *; Nikhashemi, Seyedrajab *; Javan, Nariman (Emerald, 2017)
This study aims to examine the role of knowledge management (KM) enablers on KM activities in the context of Malaysian small and medium-sized enterprises (SMEs). The effects of organizational culture, transformational leadership, organizational structure, and technology utilization as infrastructural KM enablers are examined on KM activities as knowledge acquisition, knowledge conversion, application, and protection. A total of 227 responses from SMEs’ top management are used to assess the measurement and structural models applying partial least squares-structural equation modelling (PLS-SEM). The results show that technology utilization and organizational structure are two main factors in KM activities (all structural relationships are supported). Surprisingly, organizational culture is only associated with knowledge conversion and protection and the findings indicate no relationships between organizational culture and knowledge acquisition and application. The results also indicate a positive relationship between transformational leadership and knowledge acquisition and the hypotheses on the association between transformational leadership and knowledge conversion, application, and protection are rejected. The results of importance-performance map analysis (IPMA) imply that technology utilization has the highest importance on knowledge acquisition, conversion, and protection while organizational structure has the highest importance on knowledge application. The results of IPMA also show that organizational culture has the highest performance on all KM activities. This study is amongst the few that examines the structural relationships between organizational factors and KM activities in a SME context.